Towards a monthly business cycle chronology for the euro area - Emanuel Mönch; Harald Uhlig (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
This paper is an exercise in dating the Euro area business cycle on a monthly basis. Using a quite flexible interpolation routine. we construct several monthly series of Euro area GDP, and then apply the Bry-Boschan (1971) procedure. To account for the asymmetry in growth regimes and duration across business cycle phases, we propose to extend this method with a combined amplitude/phase-length criterion ruling out expansionary phases that are short and flat. Applying the extended procedure to US and European data, we are able to replicate approximately the dating decisions of the NBER and the CEPR.
Keywords: B41; C22; C82; E32; E58; 330; business cycle; European business cycle; Euro area; Bry-Boschan; NBER methodology; Konjunktur; Konjunkturzusammenhang; EU-Staaten